Geospatial technology intervention module in Learning and Facilitation (L&F) amongst form two geography students - Ganesan Mayalagu,; Mokhtar Jaafar,; Lam, Kuok Choy; Mohd Izwan Mahmud,; Manalan Rajoo, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Technological evolution in the 21st Century Learning and Facilitation (L&F) have been significantly affirmed by the Ministry of Education Malaysia (MOE). Nonetheless, the present scenario still indicates the snag of technological development in the education system such as the application of geospatial technology in the subject of Geography in Malaysia which is not significant. Generally, Learning and Facilitation (L&F) of Geography subjects concern conventional activities that do not help much in improving the Spatial Thinking Skills (STS) and student interest. Ergo, Geospatial technology has been observed to have the potential to increase STS and student interest in Geography subjects. This study aims to develop a Geospatial technology intervention module based on the theory of Cognitive Learning, Theory of Constructivism and Bloom’s Taxonomy Theory. The formation of this module adopts Sidek Module Construction Model (MPMS) as the main motivation to complete this module. The contents of the module are also identified through a more comprehensive and analytical and extensive review of past studies done. This study creates draft modules that have four submodules namely Geography Skill, Physical Geography, Human Geography and Area Geography. The module is anticipated to be implemented as an effective L&F material especially in enhancing STS and attracting students to Geography subjects.